Analisis Pengaruh Pertumbuhan Ekonomi Dan Inflasi Terhadap Tingkat Kemiskinan Di Kabupaten Hulu Sungai Tengah - Rahda; Nur, Muhammad Anshar (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
This study aimed to determine the effect of economic growth and inflation on the level of poverty in the Tegah Hulu Sungai Regency. The research object is limited to the variables of economic growth and inflation as independent variables and the level of poverty as the dependent variable. The study results obtained simultaneously (together) show that economic growth and inflation affect poverty in the Hulu Sungai Tengah district (2005-2016). The inflation variable has a positive influence on poverty in the Hulu Sungai Tengah Regency, and economic growth does not affect the level of poverty in the Hulu Sungai Tengah Regency.